Applying Digital Storytelling for Anti-Violence Education among Vulnerable Children in Marginal Communities - Destari, Dina (Journal Ligundi of Community Service, 2025)
Background. Violence against vulnerable children in marginal communities often stems from systemic neglect, poverty, and lack of accessible educational resources. Traditional approaches to anti-violence education have struggled to engage these children effectively. Digital storytelling, with its interactive and narrative-based format, offers a promising alternative to foster empathy, awareness, and resilience by giving children a voice and a safe medium for expression. Purpose. This study aimed to examine the effectiveness of applying digital storytelling as an educational tool to promote anti-violence awareness and behavioral change among vulnerable children in marginal communities. Specifically, it explored how digital storytelling can enhance self-expression, empathy, and non-violent conflict resolution. Method. Using a mixed-methods approach, the study involved the development of digital storytelling modules tailored to children aged 8–12 in selected marginal communities. Data were collected through pre- and post-intervention surveys, focus group discussions, and teacher observations. The quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis. Results. The findings reveal that children who participated in digital storytelling activities demonstrated significant improvements in anti-violence knowledge, emotional expression, and collaborative problem-solving skills. Teachers reported greater classroom harmony and reduced instances of aggressive behavior. Qualitative insights indicated that children felt more empowered to share their personal experiences and developed stronger empathy toward peers. Conclusion. The study highlights the potential of digital storytelling as an inclusive and impactful strategy for anti-violence education in marginal communities. By integrating digital narratives into child-centered learning, educators and community workers can cultivate safer, more empathetic environments that support both personal growth and community resilience.